Severe COVID-19 multisystem inflammatory syndrome versus severe dengue in children from Indonesia: a cross-sectional study - Anggraini Alam; Fina Meilyana Andriyani; Stanza Uga Peryoga (International Journal of Emergency Medicine, 2024)
Abstract Introduction Severe multisystem inflammatory syndrome in children (MIS-C) and severe dengue are challenging to identify during the COVID-19 pandemic in dengue-endemic areas. Fever, multiorgan involvement, and shock characterize both severe MIS-C and severe dengue. Distinguishing between the two diseases is beneficial in initiating proper management. Methods Medical records of children < 18 years old who were hospitalized at Hasan Sadikin General Hospital’s PICU between December 2020 and July 2022 with severe MIS-C or severe dengue were recorded. Differences were assessed using comparative and descriptive analyses. Results Seventeen severe dengue patients and 4 severe MIS-C were included. The average age of severe MIS-C was 11.5 years (SD ± 2.9, 95% CI), and that of severe dengue patients was 6.2 years (SD ± 4.4, 95% CI) (p value = 0.034, 95%). Fever and abdominal pain were the most common symptoms in both groups (p = 0.471, 95% CI). Rash (p = 0.049) and nonpurulent conjunctivitis (p = 0.035) were two symptoms with significant differences. The highest platelet count (p-value = 0.006, 95% CI), AST (p-value = 0.026, 95% CI), and D-dimer level (p-value = 0.025, 95% CI) were significantly different between the two cohorts. Cardiac abnormalities were found in all (100%) severe MIS-C patients, but only one (5.9%) in severe dengue patients. Conclusion Age, rash, nonpurulent conjunctivitis, platelet count, AST and D-dimer level may distinguish severe MIS-C from severe dengue fever.